Evolution of the JAK-STAT pathway - Liongue, Clifford (Landes Bioscience, 2013)
The JAK-STAT pathway represents a finely tuned orchestra capable of rapidly facilitating an exquisite symphony of responses from a complex array of extracellular signals. This review explores the evolution of the JAK-STAT pathway: the origins of the individual domains from which it is constructed, the formation of individual components from these basic building blocks, the assembly of the components into a functional pathway, and the subsequent reiteration of this basic template to fulfill a variety of roles downstream of cytokine receptors.